Stochastic dynamics of a few sodium atoms in a cold potassium cloud - Bhatt, Rohit Prasad; Kilinc, Jan; Höcker, Lilo; Jendrzejewski, Fred (Arxiv, 2021)
We report on the stochastic dynamics of a few sodium atoms immersed in a cold potassium cloud. The studies are realized in a dual-species magneto-optical trap by continuously monitoring the emitted fluorescence of the two atomic species. We investigate the time evolution of sodium and potassium atoms in a unified statistical language and study the detection limits. We resolve the sodium atom dynamics accurately, which provides a fit free analysis. This work paves the path towards precise statistical studies of the dynamical properties of few atoms immersed in complex quantum environments.
Gesehen am 11.03.2021